Recovery of Proteins from Sweet Potato Cell Liquid by Acidification via Inoculation-Enhanced Fermentation and Determination of Functional Properties of Protein Products - Qingshuai Li; Liping Liu; Yanlei Han; Xiangying Zhao; Mingjing Yao; Jing Ma; Mo Han; Jiaxiang Zhang (Polish Journal of Food and Nutrition Sciences)
Starch production from fresh sweet potatoes generates process wastewater called sweet potato cell liquid (SPCL), which is rich in sweet potato protein (SPP). Currently, the commonly used protein recovery methods, such as isoelectric point precipitation and ultrafiltration, were not suitable for SPP recovery due to the low protein content of SPCL and the high cost of recovery. The feasibility of recovering SPP by SPCL acidification via inoculation-assisted fermentation was investigated in this study. The results indicated that the pH of SPCL could be reduced to approximately 4.0 within 6 h of fermentation with inoculation, resulting in an SPP extraction yield of 55.45% and purity of 66.23 g protein/100 g. With the addition of heating treatment, the extraction yield of SPP increased to 76.97–95.34%, while it maintained the purity of 66.36–70.12 g protein/100 g. The composition analysis revealed that SPP products contained sugars (below 11.5 g/100 g) in addition to protein and trace amounts of lignin and phenolics. Functional properties analysis showed that the SPP recovered by inoculation-enhanced fermentation exhibited better emulsifying and foaming properties, and higher digestibility compared to the SPP precipitated using hydrochloric acid. The method of extracting SPP from SPCL by inoculation-enhanced fermentation, as developed in this study, was a straightforward and cost-effective process that fosters significant potential for industrial applications.